Preliminary macroseismic survey of the 2016 Amatrice seismic sequence - Mariano Angelo Zanini; Lorenzo Hofer; Flora Faleschini; Paolo Zampieri; Nicola Fabris; Carlo Pellegrino (Annals of Geophysics, 2016)
After the recent destructive L’Aquila 2009 and Emilia-Romagna 2012 earthquakes, a sudden Mw 6.0 seismic event hit Central Italy on August 24, 2016. A low population density characterizes the area but, due to its nighttime occurrence, about 300 victims were registered. This work presents the first preliminary results of a macroseismic survey conducted by two teams of the University of Padova in the territories that suffered major damages. Macroseismic intensities were assessed according to the European Macroseismic Scale (EMS98) for 180 sites.